استخدام تحليل الانحدار لتحديد سلوك التكاليف الصناعية غير المباشرة: Using regression Analysis to determine the behavior of the factory overhead costs (Journal of Accounting and Financial Studies ( JAFS ), 2020)
That our focus on cost industrial indirect lies in the fact that the relative importance of these costs compared with elements other costs have increased significantly and in the environment of modern industrial and multiple clauses due to reliance on mechanization high in production and that led to lower cost labor as a natural result of the use of machinery and equipment of high-tech programmed, which requires control and tighten control on this type of an attempt by officials costs reduced to its borders possible requirement to maintain quality.The method is simple linear regression and multiple, one efficient and effective methods to achieve these goals in the light of modern environmental conditions and neglected used by most of our industrial facilities, where is the appropriate way to determine the behavior of industrial indirect costs.